Comparative Analysis of Ni- and Ni0.9Pt0.1-Ge0.9Sn0.1 Solid-State Reaction by Combined Characterizations Methods. (20th July 2018) - Quintero, Andrea; Gergaud, Patrice; Aubin, Joris; Hartmann, Jean-Michel; Chevalier, Nicolas; Reboud, Vincent; Cassan, Eric; Rodriguez, Philippe
Abstract : A comparative study of the solid-state reaction between Ni and Ni0.9 Pt0.1 thin films with Ge0.9 Sn0.1 layers was carried out. The solid-state reaction between Ni(Pt) and Ge0.9 Sn0.1 was monitored by ex-situ X-ray diffraction (XRD). Results were complemented by atomic force microscopy (AFM) and sheet resistance (R sh ) measurements. These latter evidenced that Pt addition improves both morphological and electrical properties of the layers at high temperature. Concerning the phase formation sequence, for both systems, a sequential growth was observed in which the first phase to form was a Ni(Pt)-rich phase (Ni(Pt))5 (Ge0.9 Sn0.1 )3 . Then, the mono-stanogermanidephase Ni(Pt)(Ge0.9 Sn0.1 ) appeared at the expenses of the metal-richone. For the Ni system Sn segregation was observed at 350 - 400 °C, while Pt addition delayed this segregation until 450 °C, increasing the process window for which the mono-stanogermanide phase was stable.